2020
DOI: 10.1002/fsn3.1661
|View full text |Cite
|
Sign up to set email alerts
|

Greener pathway toward the synthesis of lichen‐based ZnO@TiO2@SiO2 and Fe3O4@SiO2 nanocomposites and investigation of their biological activities

Abstract: A green way is introduced to biosynthesis of ZnO@TiO2@SiO2 and Fe3O4@SiO2 nanocomposites using the bioactive potential of Lecanora muralis (LM) lichen. UV‐Vis spectroscopy and GC–Mass analysis of the lichen show the presence of various bioactive constituents inside the lichen aqueous extract. The XRD, SEM, EDS, and elemental mapping techniques revealed the well fabrication of biosynthesized nanostructures. Also, investigation of antibacterial and antifungal activities of nanostructures demonstrated that green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…TEM analysis and selected area diffraction (SAD) confirmed the formation of silver nanoparticles. Abdullah et al (2020) used one-pot green synthesis method for the green synthesis of ZnO/TiO 2 /SiO 2 and Fe 3 O 4 /SiO 2 nanoparticle composites using the lichen Lecanora muralis. XRD, SEM, EDS, and elemental mapping techniques revealed the fabrication of biosynthesized nanostructure.…”
Section: Lichen-derived Nanoparticles: Methodologies and Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…TEM analysis and selected area diffraction (SAD) confirmed the formation of silver nanoparticles. Abdullah et al (2020) used one-pot green synthesis method for the green synthesis of ZnO/TiO 2 /SiO 2 and Fe 3 O 4 /SiO 2 nanoparticle composites using the lichen Lecanora muralis. XRD, SEM, EDS, and elemental mapping techniques revealed the fabrication of biosynthesized nanostructure.…”
Section: Lichen-derived Nanoparticles: Methodologies and Approachesmentioning
confidence: 99%
“…Alavi et al (2019) observed that Protoparmeliopsis muralisdriven metal (Ag and Cu) and metal oxide (TiO 2 , ZnO, and Fe 3 O 4 ) nanoparticles exhibited antibacterial, antibiofilm, antiquorum sensing, and antioxidant abilities against multidrug-resistant bacterium S. aureus and reference bacteria E. coli and P. aeruginosa. Abdullah et al (2020) examined Lecanora muralis-driven nanocomposites of Fe 3 O 4 /SiO 2 and ZnO/TiO 2 /SiO 2 for their antimicrobial and antifungal properties and reported that they exhibited good bioactivity against three species of pathogenic bacteria (S. aureus, E. coli, and Pseudomonas spp.) and five species of fungi (Candida albicans, Candida spp., Aspergillus flavus, Aspergillus niger, and Aspergillus terreus).…”
Section: Antimicrobial Nature Of Lichen-derived Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdullah et al introduced the green synthesis method of ZnO@TiO 2 @SiO 2 and Fe 3 O 4 @SiO 2 nanocomposites (NCs) utilizing the novel lichen species Lecanora muralis [ 164 ]. Lichen specimens were collected from Grdmandil mountain and the chemical compositions of the rock-inhibiting lichen samples were analyzed via XRD assay.…”
Section: Lichens As Biosynthesizers For Nanoparticlesmentioning
confidence: 99%
“…Abdullah et al studied the antibacterial and antifungal activities of both ZnO@TiO 2 @SiO 2 and Fe 3 O 4 @SiO 2 NCs synthesized by Lecanora muralis against S. aureus , E. coli , Pseudomonas sp., and five species of fungi, i.e., Candida albicans , Candida spp., Aspergillus flavus , Aspergillus niger , and Aspergillus terrus , utilizing both disk diffusion and agar well diffusion assays and compared the results with those of lichen extract alone [ 164 ]. Both NCs showed higher inhibitory activity than lichen extract alone against bacterial and fungal species, with the exception of the three species of the genus Aspergillus (zero inhibition zone).…”
Section: Prospective Applications Of Lichen-based Nanoparticlesmentioning
confidence: 99%